Efektivitas Metode Numbered Head Together untuk Meningkatkan Maharah Kalam Siswa Kelas VII di MTs Mamba'us Sholihin Gresik - andrian, Azril (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2025)
Speaking is a basic skill in Arabic language education, but it is often the weakest skill possessed by students, especially in the early grades of junior high school. Observations in first grade